Without crossing a border: Malaysia aims mobility on students intercultural experience during the covid-19 pandemic - Ismail, Isma Rosila; Yusof, Yusnita; Zainuddin, Zaliha; Yushriman, Yus Sharmiza (GADING Journal for the Social Sciences, 2023)
Mobility programs have been changed to online or virtual to overcome traveling restrictions due to the COVID-19 pandemic. Virtual mobility (VM) programs have been introduced to foster mobility experiences during the pandemic. Intercultural experience is usually connected with mobility programs overseas. However, the participants may have varied intercultural experiences during the VM program. This study will explore the intercultural experiences of outbound tourism students during their participation in The Asian International Mobility for Students (AIMS) program from 2020 to 2021. This study also discusses the advantages and disadvantages of online AIMS program. E-interview or online interviews are employed with a purposive sample of 13 AIMS outbound tourism students from a university in Terengganu. This study shows that the students experience dissatisfaction with online mobility and restricted opportunities in making their intercultural experience. However, they stated that this program brings more advantages than disadvantages despite all the restrictions during the COVID-19 pandemic.